Health worker performance in the management of paediatric fevers following in-service training and exposure to job aids in Kenya - Wasunna, B; Zurovac, D; Bruce, J; Jones, C; Webster, J; Snow, R (BioMed Central, 2010)
BACKGROUND: Improving the way artemether-lumefantrine (AL) is provided to patients attending clinics is critical to maximize the benefit of this new medicine. In 2007, a new initiative was launched in one part of Kenya to improve malaria case-management through enhanced in-service training and provision of job aids. METHODS: An evaluation of the intervention using pre- and post-intervention cross sectional health facility surveys was conducted in Bondo district. The surveys included: audit of government health facilities, health worker structured interviews and exit interviews with caretakers of sick children below five years of age. The outcome indicators were the proportions of febrile children who had AL prescribed, AL dispensed, and four different dispensing and counseling tasks performed. RESULTS: At baseline 33 government health facilities, 48 health workers and 386 febrile child consultations were evaluated. At follow-up the same health facilities were surveyed and 36 health workers and 390 febrile child consultations evaluated. The findings show: 1) no health facility or health worker was exposed to all components of the intervention; 2) the proportion of health workers who received the enhanced in-service training was 67%; 3) the proportion of febrile children with uncomplicated malaria treated with the first-line anti-malarial drug, artemether-lumefantrine (AL), at health facilities where AL was in stock increased from 76.9% (95%CI: 69.4, 83.1) to 87.6% (95% CI: 82.5, 91.5); 4) there were modest but non-significant improvements in dispensing and counseling practices; and 5) when the analyses were restricted to health workers who received the enhanced in-service training and/or had received new guidelines and job aids, no significant improvements in reported case-management tasks were observed compared to baseline. CONCLUSION: In-service training and provision of job aids alone may not be adequate to improve the prescribing, dispensing and counseling tasks necessary to change malaria case-management practices and the inclusion of supervision and post-training follow-up should be considered in future clinical practice change initiatives.